Comparison of Mathematical Modelling Skills of Secondary and Tertiary Students - Annapurna ramakrishna sinde, Nancy Thomas (Mathematical Statistician and Engineering Applications, 2022)
One of the pillars of scientific endeavor is the use of mathematics to model actual physical or natural processes. Inconsistencies and considerable variations in the analyses and representations or pictures of mathematical modeling are found in previous studies, according to a review of such works. New definitions of a system are created, such as "real-world problem," "mathematical problem," and "mathematical solution," as well as "modeling one system as another" and "connecting a real-world problem to a mathematical problem." This study's main aim is to find out if there are any variations in the mathematical modeling abilities of secondary and tertiary students attending a highly intellectual university, as well as what those differences are. To do this, we evaluated students' modeling abilities using a multiple-choice question instrument that has been widely utilized in experimental investigations at several universities.